KEPATUHAN KUNJUNGAN ULANG AKSEPTOR KB INTRA UTERINE DEVICES (IUD) - Tri Budi Rahayu (Bajang Institute, 2023)
Interjection of compliance control for IUD user especially from middle and low educational background. Complete understanding will lead to high level of interest and compliance control and will be increasing scoupe of IUD user as a goverment program for long term birth control. Purpose of this research is understanding compliance control of IUD user. Research is a descriptive research with cross sectional approach. Sampling methods is saturated samples from 60 IUD users. Result show 19 (31,7%) of IUD users obey, 41 (68,3%) disobey. Result shows that IUD users obey to control dominate by high school background 9 (15%), 20-30 years old 13 (21,7%) and has occupational as a worker 15 (25%). Compliance rate controls of IUD acceptors in the non compliant category.